Pengaruh Pelatihan, Motivasi, dan Lingkungan Kerja terhadap Kinerja Pegawai - Raihan Arafah; Benny Gunawan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of training, motivation, and work environment on employee performance. A quantitative approach was used, with multiple linear regression analysis techniques to measure the relationship between these variables. The population of the study consisted of employees from the Transportation Policy Agency, with a sample of 181 respondents. The results showed that training, motivation, and work environment have a positive and significant effect on employee performance, both partially and simultaneously. Effective training helps improve employees' skills and knowledge, while high motivation provides the drive to achieve work goals. A supportive and conducive work environment enhances employee comfort, leading to improved productivity, efficiency, and work quality. All these factors play a crucial role in creating an innovative and adaptive work culture. Therefore, the implementation of proper training, effective motivation, and a comfortable work environment can be an effective strategy for improving employee performance and supporting the company's competitiveness in the era of globalization.